ANALISIS PERILAKU KONSUMEN DALAM MEMILIH PRODUK TABUNGAN PERBANKAN DI KOTA PEMATANG SIANTAR - Irmawani Purba; Irsad Lubis (Departemen Ekonomi Pembangunan USU, 2013)
Consumers in choosing the bank savings products Siantar City. Products, Promotions, Savings Account, distance location, reliability Banks were selected to determine the factors most dominant factor Consumer/ Customer choose to save in the bank. Analysis Descriptive analyzes were performed using SPSS version 17.0 software. The analysis in question include tables, cross tabulations (cross tab), frequency and pictures. Consumer/Customer selected as respondents of this study were as many as 50 people who work as special civil servants who are in four agencies, namely the Department of Culture and Tourism in the District Pematang Kingdom, Revenue District Office Simalungun, SD 096 750 Kandangan in District Pematang Bandar, and in the Office Mayor Siantar Siantar City.The results obtained showed that the Consumer / Customer more likely to choose products that are offered in the Savings Bank. It can be concluded that the most dominant factor in choosing Savings Products Banking is bank product itself than other factors so that the driver softheir savings in the bank.Keywords: Saving Decisions, Product, Promotion, Savings Account, distance location, bonafides Bank.